Convoluted intake distortion measurements using stereo particle image velocimetry - Gil-Prieto, Daniel; MacManus, David G.; Zachos, Pavlos K.; Tanguy, Geoffrey; Menzies, Kevin R. (Cranfield University, 2017)
The unsteady distorted flowfields generated within convoluted aeroengine intakes can compromise the engine performance and operability. Therefore, there is a need for a better understanding of the complex characteristics of the distorted flow at the exit of S-shaped intakes. This work presents a detailed analysis of the unsteady swirl distortion based on synchronous, high-spatial-resolution measurements using stereoscopic particle image velocimetry. Two S-duct configurations with different centerline offsets are investigated. The high-offset duct shows greater levels of dynamic and steady swirl distortion and a notably greater tendency toward bulk swirl patterns associated with high swirl distortion. More discrete distortion patterns with locally high swirl levels and the potential to impact the engine operability are identified. The most energetic coherent structures of the flowfield are observed using proper orthogonal decomposition. A switching mode is identified that promotes the alternating swirl switching mechanism and is mostly associated with the occurrence of potent bulk swirl events. A vertical mode that characterizes a perturbation of the vertical velocity field promotes most of the twin swirl flow distortion topologies. It is postulated that it is associated with the unsteadiness of the centerline shear layer.